The stability and coalescence of hydrate in mineral oil emulsion. (16th September 2020) - Wu, Yi; Lv, Zhenbo; Shang, Liyan; Wang, Zhe; Liu, Baoyu; Wei, Liwa
Abstract: In the petroleum and industrial fields, hydrates are easily formed in the process of oil and gas transportation, which affects the normal operation of pipelines and even causes safety accidents. The formation of hydrates in four different oily white oil emulsion systems of 20%, 30%, 40% and 50% was compared. The change of emulsion chord length before and after hydration reaction was studied, and the mechanism of hydrate slurry formation and coalescence was explained. In the low water content system, the water-in-oil emulsion system tended to be stable under the influence of the interface and interface charge.